Enriquecimento da carne do peito de codornas europeias com ácidos graxos poli-insaturados ω-6 e ω-3 suplementadas com diferentes fontes lipídicas - Cavalcante, Cecylyana Leite (2020)
The increasing valuation of animal foods as a functional product has aroused interest in improving the profile of meat fatty acids for human consumption by supplementing diets with sources of polyunsaturated fatty acids (PUFAS). The aim of this study was to evaluate comparatively the influence of different sources of PUFAS in the diet on the fatty acid profile of quail meat. 280 European quails, average weight 90.97 ± 0.5 g, were used. During a growing period, from 14 to 42 days old, distributed in a completely randomized design with seven treatments, and five replications with 8 birds each. The quails were fed diets containing 2% of the following sources and lipid mixtures: 1. Soy oil (OSJ); 2. Linseed oil (OLI); 3. Pará nut oil (OCP); 4. Fish oil (OPX); 5. OLI + OSJ; 6. OCP + OSJ; and 7. OPX + OSJ. Performance measures, carcass yield, meat quality characteristics (chemical composition, pH, loss by centrifugation, weight loss by cooking, shear strength and color), and the fatty acid profile of lipid sources, diets and quail meat. Performance measures (weight gain, feed intake and feed conversion) were influenced by lipid sources, quails fed the OCP (18.27), OLI (17.58) and OPX + OSJ mix (17.70) ) presented higher feed consumption. The carcass yield and the chemical composition of the meat showed no significant difference (P> 0.05), while the chemical and physical characteristics showed a difference between the lipid sources supplemented in the diet. The types of oil influenced the fatty acid profile of the meat, with higher amounts of polyunsaturated fatty acids in diets that received linseed oil (35.60%) and soybean oil (33.30%) isolated, standing out also the OLI diets with the presence of linolenic acid (8.18%) and OPX presented important fatty acids that are beneficial to health, such as eicosapentanoic acids (2.58%) and docosahexaenoic acids (2.83%), which were present also in the OPX + OSJ diet, with about 1.17 and 0.25% respectively. In general, it was possible to enrich the breast meat of quail with fatty acids present in the diet. When handling it with a fish lipid source, it was enriched with EPA and DHA, while flaxseed oil served the purpose of raising the level of linolenic acid.